(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to examine the relationship between perceived stress and nomophobia among a sample of young people in Saudi Arabia, as well as to identify differences in the average scores of perceived stress and nomophobia among the sample members in terms of age. The study sample consisted of 316 young males and females selected randomly. The descriptive approach was adopted. Research data was collected using the Perceived Stress Scale and the Nomophobia Scale. The results indicated that there is a statistically significant positive correlation between perceived stress and nomophobia. There are significant differences in the average scores of perceived stress in terms of age for those who range (18-23).